Rembrandt – Biblical Interpreter - Dorot, Ruth (Journal of Education Culture and Society, 2022)
Aim. This article seeks to show that Rembrandt is the most profound, comprehensive and reliable interpreter – not an illustrator – of the Old Testament: "His ability… makes him one of the great visual interpreters of Scripture… a theologian not by academic degree but in his very nature” (Parker, 1994, p. 28). It is the purpose of this article to demonstrate the acute difference between Rembrandt’s depictions of Old Testament events and those by other artists who merely converted the overtly stated text in the Holy Bible into the visual medium. Methods. The case for claiming that Rembrandt interpreted rather than merely depicted the Old Testament will be made by analysing five of his works and the comparison to others portraying the same events. Rembrandt’s unique methods and techniques such as adding or omitting certain figures or details, using chiaroscuro extensively and deviating from expected iconography will be demonstrated as he unearths the core significance of each event. Results. This article manifests how Rembrandt whose production of artwork relating to Old Testament scenes was prolific did not merely depict Old Testament scenes but rather interpreted the deeper, psychological meanings of the subjects involved and events portrayed, exhibiting a profound understanding of the messages in the original Hebrew text. Conclusion. The article unfolds Rembrandt’s significant artistic accomplishments surpassing those who preceded or succeeded him. It reveals the different means he used in each painting expressing its high point according to Old Testament interpretation rather than through the prism of the New Testament.